Growth inhibition by transforming growth factor beta (TGF-beta) type I is restored in TGF-beta-resistant hepatoma cells after expression of TGF-beta receptor type II cDNA. - Inagaki, M (1993)
The growth of human hepatoma Hep 3B cells is potently inhibited by TGF-beta 1 (ID50 = 0.2 ng/ml, 8 pM). A mutant cell line was derived that was not inhibited in growth by TGF-beta 1 at 5 ng/ml (200 pM) and that lacked TGF-beta receptor type II (TGF-beta RII) gene. Transfection of the cloned cDNA for human TGF-beta RII to this mutant cell line restored receptor expression as well as the inhibition in growth by TGF-beta 1. In both wild-type and mutant cells stably transfected with TGF-beta RII cDNA, TGF-beta RII coimmunoprecipitated with TGF-beta receptor type I in the presence of ligand. These experiments provide direct evidence for the role of TGF-beta RII in the inhibitory effect of TGF-beta on growth and suggest that TGF-beta RII acts by means of a heteromeric surface complex with TGF-beta receptor type I.